A Further Examination of the Impact of Corporate Social Responsibility and Governance on Investment Decisions - Cohen, Jeffrey (Journal of business ethics, 2017)
The value relevance of corporate social responsibility (CSR) performance disclosures for financial markets participants remains uncertain despite advances in the literature and the recent proliferation of CSR disclosures around the world. Using an experimental approach involving MBA students at universities in the United States and Lebanon, we study the value relevance of CSR disclosures by testing whether they affect participants’ personal portfolio management investment decisions. We also examine whether the degree to which the CSR disclosures affect these decisions is influenced by corporate governance quality. To examine these issues, we examine the effect of environmental performance on investment decisions in Experiment 1, and the effect of labor performance on investment decisions in Experiment 2. Results from both experiments show that investment decisions are affected by CSR performance. Analysis shows that governance strength exerts a marginal effect on the investment decision only when CSR performance is strong. Lebanese participants appear to be more sensitive to weak performance (both CSR and governance) than U.S. participants. Overall, our findings extend the CSR disclosures literature by documenting the value relevance of CSR performance for financial markets participants’ decision making. These findings also extend the governance literature by documenting that consistent with attribution theory, the effects of governance quality are contingent upon the information and decision context, and that efforts to decontextualize governance may be counterproductive.